17β-estradiol changes the human cerebral endothelial cell proteome upon exposure to cyclic stretch - Nurul Farhana Jufri; Mohamedali, Abidali; Seong, Beom Ahn; Avolio, Alberto; Baker, Mark (Penerbit Universiti Kebangsaan Malaysia, 2018)
Hypertension and estrogen deficiency in women have been identified as significant risk factors for cerebrovascular diseases. Hypertension causes excessive vascular stretch and contributes to the initiation of cellular injury in blood vessels while estrogen has been demonstrated to exert beneficial protective effects on the vascular system. Although the specific biological outcomes exerted by either excessive stretch or estrogen exposure are well established, the combined biochemical effects of both stimuli remain unclear. Therefore, this study was conducted for quantitative proteomics study on human cerebral microvascular endothelial cells (HCMECs) subjected to 20% “pathological” cyclic stretch for a period of 18 hour in the presence or absence of 17β-estradiol by isobaric Taqs for Relative and Absolute Quantification. The results showed that only some proteins responded to 17β-estradiol (e.g., thioredoxin reductase-1), stretch (e.g., 14-3-3 protein epsilon or acidic leucine-rich nuclear phosphoprotein 32 family member B) and interestingly, some proteins returned to control pre-treatment levels when exposed to both (e.g., d-dopachrome decarboxylase, thrombospondin-1). In addition, HCMECs that exposed only to estrogen had a very similar proteomic profile (i.e., up-regulation of structural, cellular adhesion and proliferation proteins) as to those exposed to estrogen with 20% stretching for 18 hour, suggesting that estrogen ablated the detrimental effects by the stretch alone. These findings sheds light on the molecular mechanisms by which the cerebrovascular protective actions of estrogen on HCMEC exposed to pathological levels of cyclic stretch which could provide a platform for future research in therapeutic approach.